Assessing the Impact of Nutritional Knowledge and Information Sources on the Sports Performance of Elite Ethiopian Track Athletes: Insights for Optimized Sports Nutrition - Abdi Gudeta Taye; Ajita D Singh (Journal of Learning Theory and Methodology)
Background. Proper nutrition is essential for maximizing athletic performance. Athletes with a high level of nutritional knowledge are more likely to adopt healthy dietary habits, positively impacting their performance. Understanding where athletes obtain nutritional information is crucial, as these sources influence dietary practices and performance.